Morphological and Quantitative 7 T MRI of Hip Cartilage Transplants in Comparison to 3 T—Initial Experiences. Issue 9 (September 2016) - Lazik-Palm, Andrea; Kraff, Oliver; Johst, Sören; Quick, Harald H.; Ladd, Mark E.; Geis, Christina; Körsmeier, Konrad; Landgraeber, Stefan; Theysohn, Jens M.
Abstract : Objectives: The aims of this study were to evaluate morphological and quantitative 7 T magnetic resonance imaging (MRI) hip sequences in patients after acetabular cartilage transplantation and to compare image quality with 3 T MRI. Materials and Methods: Following approval from the local institutional ethics committee and signing informed consent, 9 patients with history of autologous acetabular cartilage transplantation were imaged at 7 T and 3 T MRI. Sequences (3-dimensional dual echo steady state, 3-dimensional T1 volume interpolated breath-hold examination, sagittal proton density [PD] turbo spin echo and coronal fat-saturated PD turbo spin echo, sagittal T1 mapping in dual flip angle technique, and multiecho spin echo/gradient echo sequences for T2 and T2* mapping) were applied after the intravenous application of Gd-DTPA 2− according to a protocol for delayed gadolinium-enhanced MRI of cartilage and manual B1 shimming at 7 T. Images were compared intraindividually regarding image quality and assessability of cartilage structures using 5-point scales (1 = 3 T clearly superior, 5 = 7 T clearly superior) in consensus with 2 radiologists. Contrast ratios were calculated between articular cartilage, joint fluid, and subchondral bone. An adapted MOCART (MR observation of cartilage repair tissue) score was assessed independently at 3 T and 7 T. Relaxation times were measured in the transplanted acetabular region and in 2 reference regions by 2 readers independently to calculate interreader reliability. Statistical significances of field strength comparisons were calculated using Student t test and t test for dependent measurements. Results: A 7 T MRI was superior to 3 T MRI in the majority of the sequences regarding subjective ratings. Furthermore, 7 T yielded comparable or better contrast ratios compared with 3 T. The criteria of the MOCART score matched totally at 3 T and 7 T, apart from the signal intensity of the repair tissue in PDw, which was rated higher at 7 T in 5 patients. Interreader reliability of all relaxation times was excellent. T1 and T2* relaxation times were significantly shorter at 7 T compared with 3 T. T2 relaxation times were longer at 7 T compared with 3 T without statistical significance. No significant difference could be seen when comparing the relaxation ratios (relaxation times after standardization to reference regions) of the cartilage transplant between the 2 field strengths. Conclusions: This study shows the feasibility of morphological and quantitative 7 T hip MRI in patients after acetabular cartilage transplantation and its predominant superiority regarding image quality, assessment of cartilage transplants, and contrast over 3 T MRI. To compare relaxation times between the field strengths, the calculation of intraindividual ratios is recommended.